SPIRITUAL ASPECTS AND SECURITY IN THE INFORMATION SOCIETY (Conferencea, 2022)
The issue of information security of society has always been relevant and topical for any state, it has always existed, at all times and among all peoples. Information was once a simple message, bringing one message to another. Over time, it turned into politics, became a means of fighting even for power.